2019
DOI: 10.3390/catal9060561
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance of NiO/NiTiO3 Composite Nanofiber Films

Abstract: Photocatalytic degradation of pollutants is one of the cleanest technologies for environmental remediation. Herein, we prepared NiO/NiTiO3 heterostructure nanofiber (200 nm) films by electrospinning and high temperature heat treatment, using nickel acetate and tetrabutyltitanate as nickel and titanium sources, respectively. The NiO/NiTiO3 heterostructure has advantages of good photodegradation rate constant and stability. By controlling the temperature, we can optimize the phase composition of these nanofibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In addition to these, BaTiO 3 based photocatalysts are also reported for photocatalytic organic pollutant degradation 227−232 and H 2 evolution. 233−236 Several other photocatalysts based on titanate perovskites such as MgTiO 3 , 237−239 PbTiO 3 , 240,241 NiTiO 3 , 242,243 ZnTiO 3 , 244 and FeTiO 3 245 are also reported for photocatalytic degradation of different organic pollutants. MgTiO 3 and NiTiO 3 based photocatalysts are also reported for the photocatalytic H 2 evolution reaction.…”
Section: Energy and Environmental Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these, BaTiO 3 based photocatalysts are also reported for photocatalytic organic pollutant degradation 227−232 and H 2 evolution. 233−236 Several other photocatalysts based on titanate perovskites such as MgTiO 3 , 237−239 PbTiO 3 , 240,241 NiTiO 3 , 242,243 ZnTiO 3 , 244 and FeTiO 3 245 are also reported for photocatalytic degradation of different organic pollutants. MgTiO 3 and NiTiO 3 based photocatalysts are also reported for the photocatalytic H 2 evolution reaction.…”
Section: Energy and Environmental Applicationsmentioning
confidence: 99%
“…In addition to these, BaTiO 3 based photocatalysts are also reported for photocatalytic organic pollutant degradation and H 2 evolution. Several other photocatalysts based on titanate perovskites such as MgTiO 3 , PbTiO 3 , , NiTiO 3 , , ZnTiO 3 , and FeTiO 3 are also reported for photocatalytic degradation of different organic pollutants. MgTiO 3 and NiTiO 3 based photocatalysts are also reported for the photocatalytic H 2 evolution reaction. For example, Wu et al have reported the synthesis of a ternary BaTiO 3 /Au/gC 3 N 4 heterojunction photocatalyst, wherein Au acts as an electron mediator in the involved Z-scheme mechanism .…”
Section: Energy and Environmental Applicationsmentioning
confidence: 99%
“…As we and others have previously used NiO as a co-catalyst for this CO 2 reduction, here, NiO was introduced as the co-catalyst. 89,90 This photocatalyst's photoresponse in the visible region can be attributed to the optical absorption of NiO nanoparticles deposited on the COF. Moreover, photoinduced electrons are easily promoted from the valence band (VB) to the conduction band (CB), creating holes (h+) in the valence band of the COF.…”
Section: Theoretical Investigation Of the Photocatalytic Reduction Of...mentioning
confidence: 99%
“…Formation of heterostructure, especially Z‐scheme semiconductor heterostructure, is an effectively way to promote the separation of charge carriers and remain efficient redox process, thereby promoting the photocatalytic activity . The valence band (VB) structure of ZnO and ZnS can be well matched to form a Z‐scheme heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of heterostructure, especially Z-scheme semiconductor heterostructure, is an effectively way to promote the separation of charge carriers and remain efficient redox process, thereby promoting the photocatalytic activity. [15][16]17,18,19] The valence band (VB) structure of ZnO and ZnS can be well matched to form a Z-scheme heterostructure. Actually, the conduction band (CB) edge potential of ZnO is À 0.31 eV, which is not negative enough to photocatalytic hydrogen production.…”
Section: Introductionmentioning
confidence: 99%